Monitoring and Analysis of the Adjacent Metro Shield Tunnel Deformation Caused by Simultaneous Excavation of Parallel Double Foundation Pits - Fenghua LIU (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] Simultaneous excavation of double foundation pits will affect the adjacent metro shield tunnel. In order to ensure the stability of the adjacent shield tunnel, it is necessary to monitor and analyze the deformation law of the above tunnel caused by simultaneous excavation of parallel double foundation pits. [Method] With Jianghan Road Station of Hangzhou Metro Line 6 as the engineering background, based on the on-site monitoring data of tunnel vertical displacement, horizontal displacement and convergence deformation, the effect of the simultaneous excavation of parallel double foundation pits on the adjacent shield tunnel is analyzed, and the construction risk nodes are explored. [Result & Conclusion] The long side effect of foundation pit and the concentration of unloading stress cause a larger horizontal displacement of the tunnel in the middle of the foundation pit than that on both sides of the pit. The disturbance of the soil in the early excavation area gradually superimposes with the construction of the later excavation foundation pit. As a result, the maximum horizontal displacement of the tunnel occurs in the later excavation area. The vertical displacement curve of the tunnel is characterized by two peaks and one trough due to the simultaneous excavation, erection support and pouring of the pit bottom. With the effect of eccentric unloading of the adjacent foundation pit, the convergence deformation of tunnel cross-section turns into a traverse duck egg-like shape. The simultaneous excavation of the double foundation pits paralleling to the shield tunnel produces superposition effect, and further aggravates the deformation development of the tunnel. The partitioned and layered excavation method can make good use of time and space, reduce the exposure time of foundation pit, effectively limit the rebound of soil at the bottom of the pit, thus greatly reduce the uplift of soil. Reasonable measures such as partitioning and layering, time-limited excavation, timely erection of support, and pouring reinforced concrete foundation plate can effectively reduce the influence of double foundation pit excavation on the adjacent shield tunnel.